Design of Outer-Rotor Permanent-Magnet-Assisted Synchronous Reluctance Motor for Electric Vehicles - BABA, AHMET FEVZİ (MDPI, 2021)
Today's automotive industry has focused its studies on electric vehicles (EVs) or hybrid electric vehicles (HEVs) rather than gasoline-powered vehicles. For this reason, more investment has been made in electric motors with high efficiency, high torque density, and high-power factor to be used in both EVs and HEVs. In this study, an outer-rotor permanent-magnet-assisted synchronous reluctance motor (PMaSynRM) with a new rotor topology was designed for use in an EV. The design has a transversally laminated anisotropic (TLA) rotor structure. In addition, neodymium-iron-boron (NdFeB) magnets were used in rotor topology. The stator slots were designed as distributed windings, so torque ripples are minimized. At the same time, the maximum electromagnetic torque was achieved. The analysis of the designed motor was carried out using the finite element method (FEM). Optimal values of motor parameters were obtained by improving the rotor geometry of the three-phase PMaSynRM in order to obtain maximum torque and minimum torque ripple in the design. The motor is in a 48/8 slot/pole combination, a speed of 750 rpm and a power of 1 kW. The simulation results showed that the design achieved maximum torque and minimum torque ripple.
Keywords: design; FEM; outer rotor; PMaSynRM; synchronous reluctance motor (SynRM)